Highly selective naked-eye anion sensors based on thioureido or amido calix[4]arenes - Schatz, Jürgen; Bartz, Susan; Schühle, Daniel T.; Peters, Joop A. (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2016)
Calix[4]arene-thiourea and -tetraamide nakedeye receptors do not show any tendency to self-aggregation and are highly sensitive towards small monoanions; association constants in DMSO for halogenides (chloride to iodide) and HSO4 – are < 200 M–1. Basic anions deprotonate both receptors leading to a high and selective optical readout. Binding constants for carboxylates, fluoride, and dihydrogen phosphate are three orders of magnitude higher ( 105 M–1) in case of the tetrathiourea receptor.
Keywords: amide; anion receptor; calix[4]arene; nakedeye sensor; thiourea

Hydroxy-1H-imidazole-3-oxides - Synthesis, kinetic acidity, and application in catalysis and supramolecular anion recognition - Bartz, Susan; Blumenröder, Bettina; Kern, Anika; Fleckenstein, Julia; Frohnapfel, Sabine; Schatz, Jürgen; Wagner, Alexander (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2009)
Using ab initio calculations (B3LYP 6-31G) the geometries of diethyl, dimethoxy and dimethylamino imidazolium salts were studied as representative models of imidazolium salts bearing heteroatoms directly attached to the ring nitrogen atoms of the imidazolium core units. In all cases the syn and anti arrangement of the substituents could be identified. In addition to the theoretical studies, eleven dialkoxy imidazolium salts were prepared by alkylation of six 1-hydroxy-imidazole-3-oxides using dimethyl or diethyl sulfate as strong alkylating reagents. The kinetic acidities of these compounds were studied by measuring the pseudo-first order reaction rates of the H/D exchange process of the C2-H proton of compounds 3-9. The observed kinetic acidities are much higher than reaction rates observed for simple imidazolium salts; half-lifes of the H/D exchange are usually in the range of minutes. Similar to dialkyl/aryl imidazolium salts, all prepared dialkoxy imidazolium salts could be used as precatalysts in standard aqueous Suzuki coupling reactions. In addition, two representative dialkoxy imidazolium salts could be used in supramolecular anion recognition, as demonstrated by binding studies towards iodide as guest. © 2009 Verlag der Zeitschrift für Naturforschung, Tübingen.